Exploring the effect of heat treatments on eliminating the remains of antibiotic residues (colistin) - Randa Mahmoud; Najah A. Mohamad; Abdulsalam Saleh; Saleh M. Bufarwa; Reem EL-Seifat (African Journal of Advanced Pure and Applied Sciences, 2024)
This study aims to know the effect of heat treatments on eliminating the remains of antibiotic residues, especially (colistin), as all antibiotics, especially colistin, are overused in poultry farming, and drug withdrawal times are rarely followed during the sale of meat birds or adherence to the medical prescription and consultation. The doctor, as well as there may be supervisors of the poultry houses, do not have sufficient information about the times of drug withdrawal or the danger of these residues on the health of the consumer and the danger they pose to the kidneys and body allergies. The chickens were treated by drinking water for (3) days and at (40_41_42) days old, using the antibiotic colistin, so that all chicken samples took the same dose of colistin, and the results of colistin residues showed, an estimated high-performance liquid chromatography device in the central laboratory at Omar Al-Mukhtar University. After completing the extraction of samples by us at the age of (40/41/42) days after the slaughter, in the chest muscles 67000/43000/37000 ppb, in the kidneys 61000/38000/32000 ppb, and in the liver 46000/25000/19000 ppb, and after using different thermal treatments on the tissues, it was found that The highest breakdown of these residues in the liver at the age of (40-41-42) days is 5000-3500-3000 ppb in the microwave at under 150 degrees for 20 minutes, and at the age of (41) days it is (4000 ppb) by a microwave at under 150 degrees Celsius for 20 minutes. At the age of (42) days (2500 ppb) using grilling in the oven under (180) degrees Celsius for (80) minutes, all of these results were high, which confirms that all heat treatments, whether microwave, boiling, or grilling, are unable to get rid of the remaining antibiotic residues. Here, we must focus on educating educators about the danger of these residues to human health over time and commitment to the process of withdrawing the drug and constant detection and investigation by health authorities.